Bone fragmnets of animal species from archaeological site Melnik (Vlineves) year 2000. - Mihelić, Damir; Babić, Krešimir; Brnić, Željko Trbojević Vukičević, Tajana; Hincak, Zdravka (2003)
During protecting archaeological excavation on the sarely desert near Mĕ lnik, Unetic cultural period, abundant of animal skeletal remains have been found. Preserve degree of skeletal fragments are from 1st (very good condition) to 5th (hardly identifiable) degree. After cleaning and marking, osteological material had been morphologicaly analyzed (determing the animal species, age and eventually sex), and some of the bone fragments had been x-ray analyzed. Bone fragments of large ruminants, accounted for majority of excavations ; deer 84 (23, 93%) identified bone fragments, cattle 65 (18, 51%), aurochs 14 (3, 9%) and 17 (4, 8%) bone fragments had been classified as a Bos sp. On the second place, there are bone fragments of small ruminants (sheeps and goats) 64 (18, 23%) and pigs 43 (12, 25%). In very small percentage there are skeletal remains of rabbits 18 (5, 1%), dogs 15 (5, 2%), roe deers 8 (2, 2%), horses 4 (1, 1%), and beavers, cats, hares with only 2 skeletal remains and 1 from wolf. Bone fragments may be indicator that people from Unetic cultural period from Mĕ lnik region had been cattle breeders, because we found numerous bone fragments from cattle, small ruminants and swines. Numerous bone fragments from red deer, aurochs, roe deer and hare instructed us that people of those times had been very good hunters.
Projekt MZOS
ENG